Performance of Xpert MTB/RIF and Mycobacterial Culture on Multiple Specimen Types for Diagnosis of Tuberculosis Disease in Young Children and Clinical Characterization According to Standardized Research Case Definitions. Issue 8 (13th July 2022) - Click, Eleanor S.; Song, Rinn; Smith, Jonathan P.; Mchembere, Walter; Fajans, Mark; Hariri, Parisa; Okeyo, Elisha; McCarthy, Kimberly D.; Gethi, Dickson; Odeny, Lazarus; Musau, Susan; Okumu, Albert; et al.
Abstract : Background: Tuberculosis (TB) is a leading cause of illness and death in children globally. Improved bacteriologic and clinical diagnostic approaches in children are urgently needed. Methods: In a prospective cohort study, a consecutive series of young (<5 years) children presenting with symptoms suggestive of TB and parenchymal abnormality on chest radiograph in inpatient and outpatient settings in Kisumu County, Kenya from October 2013 to August 2015 were evaluated at baseline and over 6 months. Up to 14 specimens per child were tested for the Mycobacterium tuberculosis complex by fluorescence microscopy, Xpert MTB/RIF and mycobacterial culture. Using detailed clinical characterization, cases were retrospectively classified according to standardized research case definitions and the sensitivity and specificity of microbiological tests on different specimen types were determined. Results: Among 300 young children enrolled, 266 had sufficient information to be classified according to the research clinical case definition. Of these, 36% (96/266) had TB disease; 32% (31/96) with bacteriologically confirmed intrathoracic TB. Compared to culture, the sensitivity of a single Xpert test ranged from 60 to 67% and specificity from 97.5 to 100% for different specimen types. Conclusions: Despite extensive specimen collection and laboratory testing, TB could not be bacteriologically confirmed in almost two-thirds of children with intrathoracic TB classified by research clinical case definitions. Improved diagnostic tests are needed to identify children with TB and to exclude other potential causes of illness.